Chinese Muslim Community and Pseudo-Multiculturalism in West Kalimantan, Indonesia - Ruslan, Ismail; Yusriadi, Yusriadi; Muttaqin, Imron; Hasriyanti, Nunik; Shin, Chong (Universitas Islam Negeri Mataram, 2024)
This research aims to explore pluralism in West Kalimantan, a paradoxical place in Indonesia, where multi-religious and multi-ethnic people meet. For social researchers, this situation is unique because, on the one hand, West Kalimantan is known as a conflict-prone area in Indonesia. On the other hand, part of its territory, namely the Singkawang area, is called the most tolerant area. Previous researchers assumed this situation was false because conflicts between religious and ethnic groups still occur frequently. However, the communication strategies and social interactions by ethnic groups in this area have rarely been investigated. The role of the Chinese Muslim group is significant in bringing about harmonization between the polarised groups. Chinese Muslims have provided a link that is socially very instrumental in deconstructing the firm ethnic and religious group identities and boundaries. Although they seem to form their own identity, two sides of that identity are related to religious groups and ethnic groups. Their presence thus balances inter-group communications and interactions. In conclusion, theoretically, the presence of the Chinese Muslim community in West Kalimantan breaks the ice of identity and becomes a bridge of communication between communities.